Implementasi Strategi Multisensori dalam Meningkatkan Kemampuan Membaca Anak Disleksia Kelas 2 SD Negeri Bugel 2 Tangerang - Siti Alya Solihats; Retno Andriyani; Rahma Izzatul Janah; Syahnia Maulida Fitria; Delia Syifa (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to describe the implementation of multisensory strategies in improving the early reading skills and comprehension of dyslexic children in grade 2 of Bugel 2 Public Elementary School. The subject of the study was a student with dyslexia characteristics who had shown difficulties in phonological aspects, letter recognition, reading syllables, and reading comprehension. The method used was direct observation using an early reading test instrument, a comprehension test, and a learning behavior observation sheet. The results showed that the implementation of multisensory strategies (Visual-Auditory-Kinesthetic-Tactile) through letter tracing activities, reading with the help of sounds, arranging letter cards, and reading together exercises was able to improve reading accuracy, strengthen letter-sound relationships, and foster students' self-confidence. Thus, multisensory strategies were proven effective in helping dyslexic children master early reading skills and comprehend simple texts. This study provides an important contribution to the development of more inclusive and effective teaching methods, especially for students with dyslexia, who require a more holistic and comprehensive approach to improve their literacy skills. As a suggestion, the implementation of this strategy can be expanded by involving more students and considering variations in the types of texts and teaching materials used.